Analisis Pengaruh Gaya Hidup Dan Kepuasan Pelanggan Sebagai Variabel Intervening Terhadap Keputusan Pembelian Berulang Produk Kopi Gayo Aceh Di Coffee Shop Tuku Cipete - Vivi Navila; Ambardi Ambardi (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
In Indonesia lifestyle is considered as part of secondary human needs that can change depending on the times or a person's desire to change his lifestyle. The purpose of this study is to analyze the influence of lifestyle and customer satisfaction as intervening variables on the decision to purchase Gayo Aceh Coffee Products at the Tuku Cipete Coffee Shop. This type of research is quantitative research. The object of this study is the Tuku Coffee Shop in Cipete. The independent variable in this study is lifestyle and the dependent variable is repeated purchase decisions. Meanwhile, the intervening variable is satisfaction or the link in this study is customer satisfaction. The number of samples used is using the Lemeshow formula because the population size is not known with certainty or is infinite due to the increase or decrease in visitors coming to Coffee Shop Tuku in Cipete every day. Before the analysis of hypothesis testing is carried out, the instrument quality test is carried out first, namely the Validity and Reliability Test. And then a regression analysis was carried out by first carrying out the classic assumption test, namely the Normality Test, Multicollinearity Test, and Heteroscedasticity Test. The results of this study are: Directly, there is a significant influence between lifestyle variables on customer satisfaction at Coffee Shop Tuku Cipete. Directly, there is a significant influence between lifestyle variables on consumer purchasing decisions of Coffee Shop Tuku Cipete. Directly, there is no significant influence between customer satisfaction variables on consumer purchasing decisions of Coffee Shop Tuku Cipete. Indirectly, lifestyle variables through customer satisfaction have no significant effect on consumer purchasing decisions at Coffe Shop Tuku Cipete.